2008
DOI: 10.1021/ci8001233
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Calculation of Molecular Properties from Simulation Using Kernel Molecular Dynamics

Abstract: Understanding the relationship between chemical structure and function is a ubiquitous problem within the fields of chemistry and biology. Simulation approaches attack the problem utilizing physics to understand a given process at the particle level. Unfortunately, these approaches are often too expensive for many problems of interest. Informatics approaches attack the problem with empirical analysis of descriptions of chemical structure. The issue in these methods is how to describe molecules in a manner that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…[42][43][44][45][46][47][48][49] The corticosteroid binding globulin data set was introduced in the original CoMFA paper by Cramer et al 5 and has become a common benchmark for 3D-QSAR methods. 5,9,26,48,50,51 For com- parison, we also evaluated on the Prostaglandin F2 data set published by Hopfinger et al 52 to be able to compare our method to a recently developed flexibility descriptor approach 19,20 Each data set is annotated with activity values to the specified target measured as log IC 50 or pK i .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42][43][44][45][46][47][48][49] The corticosteroid binding globulin data set was introduced in the original CoMFA paper by Cramer et al 5 and has become a common benchmark for 3D-QSAR methods. 5,9,26,48,50,51 For com- parison, we also evaluated on the Prostaglandin F2 data set published by Hopfinger et al 52 to be able to compare our method to a recently developed flexibility descriptor approach 19,20 Each data set is annotated with activity values to the specified target measured as log IC 50 or pK i .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, SVMs were mainly used for training descriptorbased models, and the development of kernels that work directly on the molecular graphs gained attention. 21,13,15,[21][22][23][24][25][26] Alternative kernel methods to support vector machines like Gaussian processes, 27 which represent a Bayesian interpretation of a kernel based algorithm, were used recently in the field of cheminformatics. 28,29 The goal of our work is to present an atom similarity measure that is capable to describe the similarity of the local structural flexibility and to show that this can be used to augment a topological similarity measure to improve the consideration of the molecular geometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal simulation studies first revealed the importance of K Na channels to the maintenance of firing accommodation of DRG neurons (Brown et al 2008b). In agreement, Nuwer et al demonstrated that siRNA knockdown of the Slack channel subunit in DRG neurons produced a loss of firing accommodation and DRG hyperexcitability (Nuwer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A more elaborate approach is the Kernel Molecular Dynamics method, introduced by Brown et al [17] This approach combines molecular interaction field techniques with information of molecular dynamics trajectories. The kernel function uses a probabilistic function to model the probe interaction potentials.…”
Section: Introductionmentioning
confidence: 99%